Clinical significance of neutrophil-lymphocyte ratio in patients with low-risk prostate cancer (Annals of Medical Research, 2021)
Aim: Active surveillance is a highly emphasized approach to low-risk prostate cancer. Upgrading and upstaging should be evaluated carefully in this strategic management. This study aimed to analyze the relationship of neutrophil-lymphocyte ratio (NLR) with these two clinical conditions.Materials and Methods: Demographic data, prostate-specific antigen (PSA) levels, prostate volumes, NLR, disease stages, and Gleason scores of 59 low-risk prostate cancer patients who underwent radical prostatectomy and met active surveillance criteria were evaluated in our clinic. The patients were examined in four groups according to their postoperative pathology specimens. Accordingly, the patients with upgrading Group 1, while those without formed Group 2. Similarly, Group 3 consisted of the cases with upstaging and the patients with no upstaging were determined as Group 4.Results: Median age, PSA levels, prostate volumes, neutrophil and lymphocyte counts of the patients were 69.0 (63.0-72.0) years, 7.24 (5.50-8.90) ng/dL, 65.0 (60.0-65.0) cc, 6.40 (4.87-8.73) K/uL, and 2.50 (1.60-3.10) K/uL, respectively. Prostate volume and age distribution were similar between the groups. PSA levels were higher in Group 1 and Group 3 than those in Group 2 and Group 4 (p=0.012 and p=0.049, respectively). NLR was 3.54 (1.89-5.45) and 1.94 (1.68-3.76) in groups 1 and 2, respectively. Although these values were low in Group 2, a statistically significant relationship could not be established (p=0.266). NLR in groups 3 and 4 was 2.46 (1.52-5.45) and 2.24 (1.68-4.35), respectively. The NLR level in Group 3 was high; however, the difference was not statistically significant (p=0.953).Conclusion: The study let us to conclude that NLR alone is not sufficient to predict the clinical course of patients with low-risk prostate cancer.
Keywords: Active surveillance; lymphocyte; neutrophil; prostate cancer